The Good Faith Of The Buyer Who Controls The Land Based On The Land Sale And Purchase Receipt (Supreme Court Decision Number 801 K / Pdt / 2022) - Rinaldi, Renitha Putri; Djajaputra, Gunawan (International Journal Labs, 2023)
In Land Law in Indonesia, valid evidence for someone to prove himself as the holder of land rights is the existence of a land certificate in which the name of the right holder is written. With the land certificate, the holder of land rights already has juridical power over the land. Through land certificates that provide juridical control, land rights holders are also entitled to physical control of the land. The position of the landholder whose name and land has been registered is strong which is guaranteed certainty and legal protection. In the event that land becomes the object of sale and purchase, there are conditions and characteristics of buying and selling land that must be met in order for the legal act to be valid. To prove that there has been a sale and purchase of land, it is necessary to prove the existence of a Sale and Purchase Deed made by the Land Deed Making Officer. With the deed, the sale and purchase of land can be registered with the Land Office to provide legal certainty and protect the buyer as the holder of new land rights. The problem is when the process of buying and selling land stops at the process of paying prices only. Meanwhile, the buyer has mastered the land based on the receipt of payment of the sale and purchase price. For this reason, it is necessary to examine the good faith of buyers in buying and selling land in cases based on Supreme Court Decision Number 801 K / PDT / 2022. This research used normative legal research, which was carried out through literature studies. Research methods in analyzing and processing data are carried out qualitatively and are descriptive analytical with deductive logic conclusions.